Characteristics of Microbial Community and Function With the Succession of Mangroves - Mai, Zhimao; Ye, Mai; Wang, Youshao; Foong, Swee Yeok; Wang, Lin; Sun, Fulin; Cheng, Hao (Frontiers in Microbiology, 2021)
In this study, 16S high-throughput and metagenomic sequencings were employed to explore the changes in microbial community and function with the succession of mangroves (Sonneratia alba, Rhizophora apiculata and Bruguiera parviflora) along Merbok river estuary, Malaysia. The sediments of the three mangroves formed their own unique dominant microbial taxa, whereby R. apiculata exhibited the highest microbial diversity. In general, Gammaproteobacteria, Actinobacteria, Alphaproteobacteria, Deltaproteobacteria and Anaerolineae were the dominant microbial classes, but their abundances varied significantly among the three mangroves. Principal co-ordinates and Redundancy analyses revealed that the specificity of microbial community was highly correlated with mangrove populations and environmental factors. The results further showed that R. apiculata exhibited the highest carbon related metabolisms, coinciding with the highest organic carbon and microbial diversity. In addition, specific microbial taxa, such as Desulfobacterales and Rhizobiales, contributed the highest functional activities related to carbon metabolism, prokaryote carbon fixation and methane metabolism. The present results provide a better understanding of the adaptations and functions of microbes in relation to environmental transition and mangrove succession in intertidal regions, the high microbial diversity and carbon metabolism in R. apiculata may in turn facilitate and maintain the formation of climax mangroves in the middle region of Merbok river estuary.